m-Quinodimethane-Based Fused-Ring Diradicals with Singlet and Triplet Ground States - Akihiro Shimizu (Chemistry)
Diradicals have attracted the attention of chemists due to their unique electronic structures and properties originating from unpaired electrons. One of the fundamental motifs of diradicals is quinodimethane; p- and o-quinodimethanes are singlet Kekulé hydrocarbons, while m-quinodimethane is a triplet non-Kekulé hydrocarbon. Most of the hydrocarbon diradicals studied to date have been limited to p- and o-quinodimethane-based non-fused-ring and fused-ring open-shell singlet diradicals and m-quinodimethane-based non-fused-ring triplet diradicals. In this account, studies on m-quinodimethane-based fused-ring diradicals, including an open-shell singlet Kekulé hydrocarbon, an open-shell singlet zwitterion, non-Kekulé hydrocarbon-based triplet diradical and diradical cation, and a triplet Kekulé hydrocarbon, are summarized. They are designed, successfully synthesized, and isolated as crystals, and their fundamental electronic structures and properties have been elucidated by optical, electrochemical, and magnetic measurements, together with DFT calculations. A series of studies showed that controlling the interaction between the two unpaired electrons of m-quinodimethane through an appropriate molecular design would produce polycyclic diradicals with various open-shell singlet diradical characters and the energy differences between singlet and triplet states.